The impact of insecticide applications on the dynamics of resistance: The case of four Aedes aegypti populations from different Brazilian regions. - Gabriela de Azambuja Garcia; Mariana Rocha David; Ademir de Jesus Martins; Rafael Maciel-; Jutta Gerlinde Birggitt Linss; Simone Costa Araújo; José Bento Pereira Lima; Denise Valle (Public Library of Science (PLoS), 2018)
In the tropics, the utilization of insecticides is still an important strategy for controlling Aedes aegypti, the principle vector of dengue, chikungunya and Zika viruses. However, increasing insecticide resistance in Ae. aegypti populations might hinder insecticide efficacy on a long-term basis. It will be important to understand the dynamics and evolution of insecticide resistance by assessing its frequency and the mechanisms by which it occurs.The insecticide resistance status of four Brazilian Ae. aegypti populations was monitored. Quantitative bioassays with the major insecticides employed in the country was performed: the adulticide deltamethrin (a pyrethroid-PY) and the larvicides, temephos (an organophosphate) and diflubenzuron (a chitin synthesis inhibitor). Temephos resistance was detected in all populations although exhibiting a slight decrease over time probably due to the interruption of field use. All vector populations were susceptible to diflubenzuron, recently introduced in the country to control Ae. aegypti. Resistance against deltamethrin was extremely high in three populations. Molecular assays investigated substitutions in the voltage gated sodium channel (NaV), the PY target site, at positions 1011, 1016 and 1534. Elevated frequencies of substitutions Val1016Ile and Phe1534Cys related to high PY resistance levels were identified. Biochemical assays detected alterations in the activities of two detoxifying enzyme classes related to metabolic resistance, glutathion-S-transferases and esterases. The results obtained were evaluated in the context of both recent insecticide use and the records of dengue incidence in each locality.The four Ae. aegypti populations evaluated were resistant to the neurotoxic insecticides, temephos and deltamethrin. However, they were still susceptible to diflubenzuron. A probable correlation between adult insect resistance to PY and the domestic application of insecticides is discussed, pointing to the need for awareness measures regarding the correct utilization by citizens. This work aims to contribute to the efficient and rational management of Ae. aegypti control of both larvae and adults.